Extraction and Fractionation of Anti-Cholesterol Compounds from Water Chestnut (Eleocharis dulcis) - Putra, Hemi Adi; Husni, Amir; Isnansetyo, Alim (Universitas Gadjah Mada, 2025)
Cholesterol is a significant contributor to mortality rates worldwide. The quest for effective cholesterol treatments continues, aiming to develop preventive agents with minimal adverse effects. This study seeks to elucidate the anti-cholesterol properties of extracts and components fractionated from water chestnut (Eleocharis dulcis). The research encompassed several phases, including sampling, extraction and fractionation, qualitative and quantitative flavonoid analysis, anti-cholesterol activity assays, and gas chromatography-mass spectrometry (GC-MS) analysis. The quantitative flavonoid assessment revealed that the highest flavonoid concentration was present in the ethyl acetate:methanol (5:5) fraction, totaling 79.224 mg/mL. The water chestnut extract demonstrated notable anti-cholesterol activity with an IC50 value of 13016.27 ± 5648.31 ppm, whereas the water chestnut fraction exhibited enhanced anti-cholesterol activity with an IC50 value of 42.22 ± 9.79 ppm, comparable to simvastatin. The bioactive compounds in water chestnut attributed to its anti-cholesterol effects include 7,9-Di-tert-butyl-1-oxaspiro(4,5)deca-6,9-diene-2,8-dione, n-Hexadecanoic acid, Octadecanoic acid ethyl ester, 9-Octadecenamide (Z)-, 9,12,15-Octadecatrienoic acid, 2,3-dihydroxypropyl ester, 3,4-Dimethoxycinnamic acid, and 2H-1-Benzopyran-2-one, 7-methoxy-. These findings suggest that the fraction derived from E. dulcis exhibits significant anti-cholesterol activity and holds promise for further development in the treatment of hypercholesterolemia.